2018
DOI: 10.20448/journal.509.2018.53.208.216
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Academic Motivation Levels of Students Study in Different Faculties in Terms of Certain Variables (Sakarya University Case)

Abstract: Entirely 1325 students participated in this research that was conducted to specify the differences between motivation levels of students in terms of age, gender, class and department variables. 'Academic Motivation Scale' that is seven points Likert scale was developed by Karaguven (2012) was used as the data collection tool in this research that was performed by screening model. Descriptive analyses were applied in data T-test was applied in independent groups to determine whether there were differences based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The discriminant validity of the constructs was assessed using the square root of AVE compared to the squared correlation among the latent constructs (Bove et al, 2009;Hair et al, 2014;Keskin & Korkutata 2018). Table 2 shows that the square roots of the AVE values are greater than the squared correlation for each construct.…”
Section: Measurement Modelmentioning
confidence: 99%
“…The discriminant validity of the constructs was assessed using the square root of AVE compared to the squared correlation among the latent constructs (Bove et al, 2009;Hair et al, 2014;Keskin & Korkutata 2018). Table 2 shows that the square roots of the AVE values are greater than the squared correlation for each construct.…”
Section: Measurement Modelmentioning
confidence: 99%
“…This makes someone more skilled and good at managing their finances. Keown (2011); Keskin & Korkutata (2018) explains that there is a relationship between the income of parents with financial knowledge. Older people with higher household incomes tend to have a higher level of financial literacy because they use financial services more often.…”
Section: Effects Of Parent Income On Financial Literacymentioning
confidence: 99%
“…Students of ages below 20 years old also showed significantly high scores in all online self-regulated learning dimensions compared to older age students. This finding indicated that younger age students had higher extrinsic motivation levels which may be because they just entered and experienced studying in university and they have high motivation to work hard and self-regulate learning for success, but as the age increases, they may steer away from this motivational level because of several different reasons such as experiences and expectations that had fall behind (Keskin & Korkutata, 2018). Third, students in lower semesters; 1 or 2, showed to have higher scores in the five online learning selfefficacy dimensions; self-efficacy in computer/internet, self-efficacy in time management, self-efficacy to interact with lecturers for online courses, self-efficacy to interact socially with classmates, and self-efficacy to interact academically with classmates.…”
Section: Ns -Not Significant Ms -Management Science Ssh -Social Scien...mentioning
confidence: 94%
“…Overall, students in lower semesters; 1 or 2, were likely to exhibit higher online learning self-efficacy which was inconsistent with studies by (Limiansi & Hadi, 2022), (Yavuzalp & Bahcivan, n.d.), and online selfregulated learning. The possible reason is, that students in lower semesters; 1 or 2, were those students who just entered the university with high levels of excitement and motivation to learn for success (Keskin & Korkutata, 2018).…”
Section: Ns -Not Significant Ms -Management Science Ssh -Social Scien...mentioning
confidence: 99%